The Effect Of (Physical - Technical) Exercises Using The High-Intensity Stations Method In Raising The Level Of Strength Characterized By Speed, Flexibility And Achievement For Junior High Jump Players - Al-Sudani, Ansam Khazal Jabbar (Indonesian Journal of Physical Education and Sport Science, 2025)
Study purpose. The performance of high jumpers is not currently meeting desired achievements, with progress stagnating despite physical development. This discrepancy is believed to stem from a weaker focus on developing motor abilities, such as flexibility, in comparison to physical training. Flexibility training, incorporating a variety of exercises, is hypothesized to be a critical component for enhancing the specific motor skills required for high jumping. Therefore, this study aimed to identify the effect of a structured flexibility training program on the level of selected motor abilities and high jump achievement in participants aged 12-14 years. Materials and Methods. The study likely involved a sample of participants aged 12-14, who were probably divided into an experimental group and a control group. The experimental group underwent a supervised flexibility training program featuring varied exercises, while the control group continued with their standard training regimen. Key motor abilities relevant to high jumping (e.g., flexibility, agility, balance) and high jump achievement (measured by jump height) were assessed for all participants before the intervention (pre-test) and after its completion (post-test). Statistical analysis was then used to compare the improvements between the two groups. Results. The results demonstrated that the group which participated in the flexibility training program showed significant improvements in the measured motor abilities and in their high jump performance compared to the control group. Conclusion, flexibility training is a successful intervention for raising the level of key motor abilities and enhancing achievement in the high jump for individuals aged 12-14 years. It is therefore recommended that coaches and trainers adopt structured flexibility training as an integral component of athletic development programs for young high jumpers.